(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the theoretical foundations and practical applications of exercise systems in foreign language teaching, focusing on the structural organization and methodological principles that govern effective language acquisition. The research analyzes various approaches to designing exercise systems, including their hierarchical arrangement, progression from controlled to communicative activities, and integration of linguistic and cultural components. By exploring both traditional and innovative exercise typologies, this study identifies key principles for developing comprehensive exercise systems that promote language proficiency across all skill areas while accommodating diverse learning styles and educational contexts.